Synthesis of a controller for quadrotors with suspended payloads - Linh, Nguyen Thi Dieu; Bang, Nguyen Van (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the control of quadrotor. Unmanned aerial vehicles currently in use often encounter various challenges and limitations. When operating in environments affected by external disturbances-particularly, when carrying suspended loads via cables, the control problem becomes significantly more complex. As a result, the quadrotor is unable to accurately follow the predefined flight trajectory. Problem that was solved is the synthesis of a new controller for the quadrotor with a cable-suspended load, ensuring that the quadrotor accurately follows the predefined flight trajectory. The proposed algorithm demonstrates a significant improvement over existing methods by effectively suppressing the oscillation angle of the suspended payload, treating the payload’s influence as an external disturbance. Furthermore, it constrains the swing angle within an acceptable range, thereby ensuring the stability and robustness of the overall system during operation. This study presents a novel control algorithm capable of guiding the quadrotor precisely to the desired position, even under the condition of carrying a cable-suspended load in a varying environment. The algorithm demonstrates a significant advantage, enabling the quadrotor to reach the desired trajectory within 2.6 seconds. The suspended load exhibits only small oscillations, which gradually diminish as the quadrotor transitions to a stable state. With its simple structure, high stability, and fast convergence, this robust solution is essential for unmanned aerial vehicles, significantly enhancing their operational effectiveness under complex conditions. A key strength of the proposed algorithm lies in its simple structure. Furthermore, it demonstrates high convergence rates and exceptional stability, crucial attributes for real-time applications. Its design also ensures ease of practical implementation, making it a viable solution for unmanned aerial vehicles. The algorithm is developed based on modern control techniques, combining a sliding mode controller with an extended state observer. The SMC maintains system stability in the presence of disturbances and uncertainties, while the ESO estimates unmeasured states and aggregated disturbances affecting the system. This design ensures accurate positioning of the quadrotor with a suspended load at the desired location